Associations between illness perceptions, word recognition, and perceived sound quality in cochlear implant users - Lehmann, Effi; Glaubitz, Cynthia; Heinze-Köhler, Katharina; Liebscher, Tim; Hoppe, Ulrich (International Journal of Audiology, 2024)
Objective: Illness perceptions refer to thoughts and ideas an individual has about an illness. The aim was to understand how cochlear implant (CI) users’ illness perceptions, in addition to their monosyllabic word recognition abilities, are associated with their self-perceived sound quality. Design: Data were collected during routine CI check-up appointments. Participants completed the Brief Illness Perception Questionnaire (assessing their illness perceptions) and the Hearing Implant Sound Quality Index (assessing their subjective sound quality). Additionally, monosyllabic word recognition abilities were measured with the Freiburg Monosyllable Word Test. Hierarchical regression analysis were utilised to model users’ sound quality ratings. Participants’ age was entered first as a control variable. In the next step, monosyllabic word recognition was entered. Finally, participants’ illness perceptions were entered. Study sample: Fifty-five participants with unilateral CI provision. Results: Monosyllabic word recognition was significant in the second step. When illness perceptions and monosyllabic word recognition were both included in the third step, illness perceptions, but not monosyllabic word recognition, were significant. The model explained 22% of the variance of subjective sound quality. Conclusions: Monosyllabic word recognition abilities and illness perceptions of CI users are important for their self-reported sound quality, but illness perceptions appear to be potentially more relevant.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Brief IPQ; Cochlear implant; HISQUI; illness perceptions; Leventhal’s Self-Regulatory Model; monosyllabic word recognition; self-reported sound quality